Examining the livelihood assets and sustainable livelihoods among the vulnerability groups in Malaysia - Ibrahim, Ahmad Zubir; Hassan, Kalthum; Kamaruddin, Roslina; Anuar, Abdul Rahim (OMJP Alpha Publishing, 2017)
Until recently, the livelihood vulnerability group such as paddy farmers, coastal fishers and rubber tappers in rural areas are susceptible to economic shock and climate change such as flood and drought. This situation will jeopardise the livelihoods of this group. In response to that, this study aims to investigate the relationship between livelihood assets and sustainable livelihoods. This study adopts quantitative study with stratified sampling method to select a total of 600 respondents from rural areas in Kedah and Kelantan. The findings confirm that physical asset, natural asset and social asset are significantly related to the achievement of sustainable livelihoods. Some recommendations have been highlighted to assist the concerned parties in improving sustainable livelihoods among the vulnerable group in rural areas.